Functional Polymer Brushes on Diamond as a Platform for Immobilization and Electrical Wiring of Biomolecules. (16th January 2013) - Reitinger, Andreas A.; Hutter, Naima A.; Donner, Andreas; Steenackers, Marin; Williams, Oliver A.; Stutzmann, Martin; Jordan, Rainer; Garrido, Jose A.
Abstract For the biofunctionalization of electronic devices, polymer brushes can provide a route which allows combining the advantages of other commonly used approaches, such as immobilization of functional biomolecules via self assembled monolayers or coated polymer matrices: high stability and loading capacity, efficient electron transport, and excellent biocompatibility. In the work presented here, poly(methacrylic acid) brushes are prepared by self‐initiated photografting and photopolymerization on diamond electrodes. In this straightforward process no prior grafting of initiators is required since the initiation of the polymerization can be conveniently controlled by the hydrogen or oxygen termination of the diamond surface. Boron doped nanocrystalline diamond as an electrode material provides extreme chemical inertness and stability, inherent biocompatibility, and superior electrochemical properties, such as the large accessible potential window and low background currents. As a proof of concept we demonstrate the amperometric detection of glucose by polymer brushes covalently modified with the redox enzyme glucose oxidase and aminomethyl ferrocene as electron mediator. Characterization by X‐ray photoelectron spectroscopy and atomic force microscopy both indicate a high loading of the ferrocene mediator. Consistently, electrochemical cyclic voltammetry shows a multilayer equivalent loading of ferrocene and highly efficient electron transfer throughout the polymer film. Overall, functionalized polymer brushes can provide a promising platform for the immobilization and electrical wiring of biomolecules for bioelectronic and biosensing applications.